Does the COVID-19 Pandemic Cause People to Be Unhappy? Evidence from a Six-Country Survey - Cuong Viet Nguyen (Global Labor Organization (GLO), 2021)
Does the COVID-19 pandemic cause people unhappy? In this study, we use a recent survey from China, Japan, South Korea, Italy, the United Kingdom and the United States to explore this question. We find a relatively large effect: a one per-mille point increase in the incidence of the COVID-19 cases increases the probability of unhappiness by 0.002. Possibly channels through which the COVID-19 pandemic causes unhappiness are negative effects on economic outcomes and social interactions of people. We also find that more disadvantaged people including poor, rural, female and older people are more likely to be affected by the pandemic.
Keywords: I30; J18; J24; 330; COVID-19; happiness; life satisfaction; income loss; job loss